SPSPACE BOOK - UNIVERSITY SPACE MANAGEMENT - Gustavo Leite Teodoro, Ryan; Silveira de Lima, Allan; Gabriel Araújo Câmara, Hercules; Murillo Siqueira Teodoro, Thales; de Souza Barbosa, Jeffrey; Cesar Godoi Dutra, Jullio; Santos Faria Silva, Talles (CIPEEX, 2024)
Imagine an academic landscape that is constantly evolving, where the insatiable desire for knowledge translates into a growing demand for classrooms, laboratories and sports spaces. As the corridors of college education fill up with eager students and curious minds, the efficient management of these spaces becomes crucial. This is the background to our project – na innovative solution designed to simplify the scheduling of university spaces. The main objective of this project is to create na efficient digital platform that allows university spaces to be booked quickly and practical. This platform will benefit students, teachers and other members of the community, offering a modern solution to an ever-increasing demand. The development of this system will follow an approach based on agile methodologies, which are known for their flexibility and efficiency. The process includes requirements analysis, design and architecture, development, testing and validation, and finally, deployment. During the requirements analysis phase, the team identifies the specific needs of the academic community in relation to the scheduling of spaces, conducting interviews and surveys to understand the main requirements of the system. Based on the requirements gathered, the user interface and the system’s architecture will be designed, with an emphasis on usability and integration with the university’s existing systems. In the development phase, system implementation will be conducted prioritizing security and efficiency, using modern web technologies to ensure a high-quality user experience. After implementation, the system will be rigorously tested to ensure that it meets the requirements and works flawlessly. Usability tests will be carried out to verify the system’s ease of use. Once successfully validated, the system will be deployed for use by the academic community. It is hoped that this system for scheduling university spaces offers considerable benefits, such as quick and easy access to space availability, simplified and efficient booking, improvement in university resources management, greater satisfaction among the academic community and a reduction in scheduling conflicts. Ultimately, in this project, we are not just creating a digital platform for scheduling university spaces, we are shaping the future of academic management. Our main objective is clear: to make it easier to book spaces in a quick and practical way. However, our objectives go beyond this fundamental goal. We want to reduce scheduling conflicts that can cause frustration and waste of resources. We want to improve the efficiency of university resource management, ensuring that each room is used in the best possible way. We want to increase satisfaction of the academic community by offering a modern solution that meets their specific needs. Ultimately, this project aims to improve the university environment, making it more conducive to the success of academic activities and the optimization of resources. We therefore invite you to explore this project, which not only simplifies, but transform the booking of university spaces.